Simultaneous analysis of drugs administered to lung‐transplanted patients using liquid chromatography–tandem mass spectrometry for therapeutic drug monitoring. (22nd January 2021) - Takasaki, Shinya; Hirasawa, Tensei; Sato, Yu; Maekawa, Masamitsu; Tsukamoto, Taku; Kikuchi, Masafumi; Ogura, Jiro; Hayakawa, Yoshihiro; Matsuda, Yasushi; Oishi, Hisashi; Sado, Tetsu; Noda, Masafumi; et al.
Abstract: Several drugs are administered to lung‐transplanted patients, which are monitored using therapeutic drug monitoring (TDM). Therefore, we developed and validated a liquid chromatography–tandem mass spectrometry method to simultaneously analyze immunosuppressive drugs such as mycophenolic acid, antifungal drugs such as voriconazole and itraconazole, and its metabolite hydroxyitraconazole. Chromatographic separation was achieved using a C18 column and gradient flow of mobile phase comprising 20 mM aqueous ammonium formate and 20 mM ammonium formate‐methanol solution. A simple protein precipitation treatment was performed using acetonitrile/methanol and mycophenolic acid‐ 2 H3, voriconazole‐ 2 H3, itraconazole‐ 2 H4, and hydroxyitraconazole‐ 2 H4 as internal standards. The linearity ranges of mycophenolic acid, voriconazole, itraconazole, and hydroxyitraconazole were 100–20, 000, 50–10, 000, 5–1000, and 5–1000 ng/mL, respectively. The retention time of each target was less than 2 min. The relative errors in intra‐ and inter‐day were within ±7.6%, the coefficient of variation was 8.9% or less for quality control low, medium, and high, and it was 15.8% or less for lower limit of quantitation. Moreover, the patient samples were successfully quantified, and they were within the linear range of measurements. Therefore, our new method may be useful for TDM in lung‐transplanted patients.